(untitled) (Research, Society and Development, 2020)
Microgreens are young vegetable plants harvested prematurely that have been gaining popularity in conventional and gourmet cooking due to their nutritional and sensory properties. This study aimed to evaluate the acceptability of microgreens of lettuce (Lactuca sativa L.), dry cress (Lepidium sativum L.), amaranth (Amaranthus caudatus L.), beet (Beta vulgaris L.), cabbage (Brassica oleracea L.) and sunflower (Helianthus annuus L.) by guests of Lapinha SPA, a physical and mental health invigoration establishment located in the municipality of Lapa, state of Paraná. To assess the acceptability of these vegetables, the rest-ingestion methodology was used. The results obtained showed that the acceptability of the species varied between 84.84% and 96.60%, being considered excellent for all offered species. The analysis of variance followed by the Tukey test showed that there was a statistically significant difference in the acceptability index, with the best accepted species in decreasing order, were the amaranth microgreens (mean left = 2.16 g), cabbage (left over) medium = 5.12 g), dry cress (leftover = 6.40 g), lettuce (leftover = 6.60 g), beets (leftover = 6.84 g), and sunflower (leftover = 9.76 g). These plants have the potential to be incorporated into the diet of customers of SPA’s establishments, since they add different nutritional and aesthetic value to the dishes offered in cooking.